Stress-Induced Functional Alterations in Amygdala: Implications for Neuropsychiatric Diseases - Zhang, Xin; Ge, Tong tong; Yin, Guanghao; Cui, Ranji; Zhao, Guoqing; Yang, Wei (Frontiers in Neuroscience, 2018)
The amygdala plays a major role in the processing of physiologic and behavioral responses to stress and is charactered by gamma-aminobutyric acid (GABA)-mediated high inhibitory tone under resting state. Human and animal studies showed that stress lead to a hyperactivity of amygdala, which was accompanied by the removal of inhibitory control. However, the contribution of hyperactivity of amygdala to stress-induced neuropsychiatric diseases, such as anxiety and mood disorders, is still dubious. In this review, we will summarize stress-induced various structural and functional alterations in amygdala, including the GABA receptors expression, GABAergic transmission and synaptic plasticity. It may provide new insight on the neuropathologic and neurophysiological mechanisms of neuropsychiatric diseases.